Meaning and Usage of Jibun in Oral Japanese - Mercy Riyanto; Hari Setiawan; Robihim Robihim (Chi'e: Journal of Japanese Learning and Teaching, 2023)
This study analyzes the meaning of using the word Jibun in spoken language taken from the story of a smartphone game entitled "Twisted Wonderland". This study uses conversational data in the game as research data. This study aims to recognize the various meanings and uses of the word Jibun in the Japanese spoken language. This qualitative research uses a descriptive method, which describes the data obtained and concludes the results through categories formed through the results of data description and analysis. Electronic games are data sources, mainly from the Heisei and Reiwa eras up to the time of this research. The result found that the use of the word Jibun as Saikikei, the use of the word Jibun as a personal pronoun, and the word Jibun as a word that refers to a general person. However, compared to the previously studied theory, some differences in usage were found. The use of Jibun as Saikikei in spoken language has differences in the order of subject positions because, in this study, the data used is part of a conversation and uses spoken language, so the word order does not match the standard language.